2014
DOI: 10.1002/2013ja019515
|View full text |Cite
|
Sign up to set email alerts
|

Transmission line model for the near‐instantaneous transmission of the ionospheric electric field and currents to the equator

Abstract: The simultaneous onset of the preliminary impulse (PI) of the geomagnetic sudden commencement at high latitude and dayside dip equator is explained by means of the TM 0 mode waves propagating at the speed of light in the Earth-ionosphere waveguide (EIW) [Kikuchi et al., 1978]. A couple of issues remain to be addressed in the EIW model: (1) How is the TM 0 mode wave excited by the field-aligned currents (FACs) in the polar region? (2) How are the quasi-steady ionospheric currents achieved by the TM 0 mode waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 49 publications
(138 reference statements)
4
73
0
Order By: Relevance
“…The initiation of both PI and MI magnetic field variations is considered to occur simultaneously across the entire latitude range including the magnetic equator, and this is attributed to rapid changes in large-scale electric fields (Boudouridis et al 2011) and their instantaneous penetration to lower latitudes (Araki 1977;Kikuchi 1986). Recently, Kikuchi (2014) presented a comprehensive model of signal transmission from the magnetosphere to the equatorial ionosphere through the ionosphere-ground waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of both PI and MI magnetic field variations is considered to occur simultaneously across the entire latitude range including the magnetic equator, and this is attributed to rapid changes in large-scale electric fields (Boudouridis et al 2011) and their instantaneous penetration to lower latitudes (Araki 1977;Kikuchi 1986). Recently, Kikuchi (2014) presented a comprehensive model of signal transmission from the magnetosphere to the equatorial ionosphere through the ionosphere-ground waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…(from Fig. 6 of Kikuchi et al 2008) terminated by the fully ionized magnetosphere (Kikuchi 2014). The positive electric potential (+V 0 ) is transmitted with the downward FAC (thick arrow) to the left end of the waveguide, providing the vertical electric field, E zV in the waveguide, which excites the TM 0 mode wave propagating with the horizontal Poynting flux, S xV , at the speed of light.…”
Section: Electric Field Transmission Mechanismmentioning
confidence: 99%
“…8 of Kikuchi et al 2008) dashed line at noon, on which downward and upward currents of the same amount are supposed to take part in the duskside and dawnside current circuits driven by the positive and negative potentials, respectively. Replacing the waveguide with the finite-length parallel plane transmission line, Kikuchi (2014) calculated the electric potential and currents in the ionosphere and showed that the ionospheric currents grow to the steady-state value with the time constant of a few to 10s of seconds, depending on the ionospheric conductivity. The transmission line model well explains the instantaneous onset of the PI at all latitudes and delayed peak at the equator by 20 s (Takahashi et al 2015).…”
Section: Electric Field Transmission Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions channelize the plasma into different magnetospheric regions like plasma sheet and ring currents eventually transporting it through reconnection in the magnetotail toward polar latitudes in the Northern and Southern Hemispheres (Baumjohann et al, 2010;Hasegawa et al, 2004;Heikkila, 2011;Kamide & Baumjohann, 1993;Ohtani et al, 2000). The electric field of interplanetary origin can instantaneously penetrate to equatorial and low latitudes (Kikuchi, 2014;Kikuchi & Hashimoto, 2016 and references therein), whereas delayed effects of high-latitude Joule heating and associated perturbation winds and traveling atmospheric disturbances (TADs) arrive after more than 8-10 hr to days (Bauske & Prölss, 1997;Dashora et al, 2009;Ding et al, 2007;Hajkowicz, 1990;Hocke & Schlegel, 1996;Hunsucker, 1982;Nicolls et al, 2004). The electric field of interplanetary origin can instantaneously penetrate to equatorial and low latitudes (Kikuchi, 2014;Kikuchi & Hashimoto, 2016 and references therein), whereas delayed effects of high-latitude Joule heating and associated perturbation winds and traveling atmospheric disturbances (TADs) arrive after more than 8-10 hr to days (Bauske & Prölss, 1997;Dashora et al, 2009;Ding et al, 2007;Hajkowicz, 1990;Hocke & Schlegel, 1996;Hunsucker, 1982;Nicolls et al, 2004).…”
Section: Introductionmentioning
confidence: 99%